PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Kasus Pada BPR. Gunung Ringgit, Malang) - Moh Zhamrudz; Muhammad Mansur; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTAlong with the advancement of the times and technological advances, humans arerequired to be able to have quality skills to meet a better standard of living.Therefore, if human resources can be utilized effectively and efficiently will beuseful to support sustainable economic growth. The problem now is how to createhuman resources that can produce productivity optimally, so that corporate goalsare achieved. The purpose of this study is to determine the extent of the influenceof motivation, work environment and organizational culture on employeeperformance in the BPR. Gunung Ringgit Malang.The purpose of this study is to know and analyze the influence of motivation, workenvironment and organizational culture on employee performance. Methods ofdata analysis in this study using quantitative methods with data managementtechniques using multiple regression analysis. Data were collected throughquestionnaires. Questionnaires are distributed to BPR employees. GunungRinggit Malang. Measurements are made with the likert scale 1 to 5. The resultshows that motivation and work environment have a significant effect onemployee performance, whereas organizational culture has a significant influenceon employee performance.Keywords: Motivation, Work Environment, Organizational Culture andEmployee Performance.